The model Of Good Teacher In The Ron Clark Story Movie Directed By Randa Haines (2006) : An Educational Psychological Perspective - GHOFAR., ABDUL (2012)
This study is aimed to show the model of good teacher and learning style that the major character has by using educational psychology. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the seconds is analyzing the movie based on the psychological analysis. This research is qualitative research; type of data of the study is text and image taken from two data sources; primary and secondary. The primary data source is The Ron Clark Story movie directed by Randa Haines released in 2006. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis, it is clear that in this movie, Randa Haines conveys a message that some individuals may have special needs corresponding to their own learning style. Secondly, based on the educational psychological analysis, it is evident that in this movie, Randa Haines expresses the educational phenomena that each person has a different learning style and model of good teacher.